Real Time Unit Monitoring Information Systems Using The Waterfall Method PT. Andhana Kirana Yasa Jakarta - Imam Budiawan; Muhammad Nasrulloh; I Ispandi (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
PT. Andhana Kirana Yasa is a company engaged in car accessories installation services. The speed in the production process and the quality of products produced become the main value to compete with competitors. But to achieve the desired quality there are still problems that are experienced, first reject the unit of production and second, there is a cripple unit (no part), which is the unit in the production process. Still, the stock parts are exhausted in the warehouse so that accessories cannot be installed. The existing problems if not handled quickly and precisely cause a decrease in productivity. The installation service company has been given a maximum target lead time of 1 unit (car) for 3 hours. To overcome this problem, a monitoring application system/program is needed, which monitors the unit's production conditions directly so that when an obstacle occurs, it can be effectively dealt with. This application program is created using the waterfall method, which has the manufacturing stages starting from Requirement Analysis, System Design, Implementation, Integration and Testing, Operation and Maintenance. The programming languages used are HTML, PHP and JavaScript, MySQL as a database, and Sublime Text Editor as an editor. The purpose of making the application program is to monitor the unit production directly against problems that occur and produce data that is used to evaluate employee performance.